RANCANG BANGUN APLIKASI ARISAN ONLINE DENGAN SMART CONTRACT UNTUK MEMINIMALISIR RESIKO PENIPUAN - Lintin, Yosep Tara; Aditya Widhiatama, Ngakan Putu; Purnama, Fajar; Shandyasa, I Wayan; Sukadarmika, Gede; Gede Manuaba, Ida Bagus; Oka Widyantara, I Made; Juliawan Pawana, I Wayan Adi (Jurnal SPEKTRUM, 2023)
Arisan is an activity that is usually carried out by housewives where each member will donate money and at each meeting there will be a lottery to hand over the money that has been collected to one of the lucky members. Usually, arisan is done regularly and offline. However, since the pandemic in 2020, many people have started doing arisan online. With the rise of arisan online activities, there are many cases of fraud with a large amount of loss and of course it cannot be ignored. Based on these problems, a platform is needed to conduct arisan online that can prevent fraud cases. This container will be made in the form of a decentralized application by utilizing blockchain technology in this case this article utilizes smart contracts on the Binance Smart Chain to ensure that after this application is published, no party will be able to make changes to the data or functions of this application to minimize frauds.